Pengaruh Kesadaran Wajib Pajak dan Sanksi Perpajakan terhadap Kepatuhan Wajib Pajak Orang Pribadi : Studi Kasus Wajib Pajak Orang Pribadi di Wilayah Kantor Pelayanan Pajak Pratama Tampan Pekanbaru - Siti Rahayu Ningsih; Evi Marlina; Muhammad Ahyaruddin (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2024)
This research aims to examine the influence of taxpayer awareness and tax sanctions on individual taxpayer compliance. In this research, the method used for data collection was a questionnaire. The population in this study is individual taxpayers registered at the Pratama Tampan Pekanbaru Tax Service Office. Sampling used the random sampling method, with a total sample of 160 taxpayers. This research is quantitative research, the data obtained was processed using SPSS version 21. The results of this research show that taxpayer awareness and tax sanctions influence individual taxpayer compliance.